Analysis of Productivity and Resource Use Efficiency of Paddy - Sudhakar, V.; Gurupandi, M. (Indian Journal of Marketing, 2008)
Agriculture is the backbone of the Indian Economy.The economic development of India mainly depends upon the agriculture sector.Nearly 65 percent of India’s population is still dependent on agriculture for livelihood and employment.It is also the source of supply of raw materials for industries and it provides support to the transport system.It also plays an important role in India’s International Trade. In recent years,there has been a great diversification of Indian agriculture such as livestock,horticulture and fisheries.